1996
DOI: 10.1063/1.363615
|View full text |Cite
|
Sign up to set email alerts
|

Annealing processes of vacancy-type defects in electron-irradiated and as-grown 6H-SiC studied by positron lifetime spectroscopy

Abstract: Annealing processes of vacancy-type defects in 3 MeV electron-irradiated and as-grown 6H-SiC have been studied by positron lifetime spectroscopy. Vacancy-type defects giving rise to a positron lifetime of 183 ps were detected in as-grown n-type specimens. They were found to be annealed at around 1400°C and were related to silicon vacancies, possibly complexes of silicon vacancies and nitrogen atoms. Defects related to carbon vacancies, silicon vacancies, and divacancies were found to be created by electron irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 18 publications
2
65
2
Order By: Relevance
“…The annealing of vacancy-related defects has been studied by positron annihilation spectroscopy (PAS) 11,12,13,14 and electron paramagnetic resonance techniques (EPR) 15,16,17,18 in irradiated material. The identification of the EPR-centers as isolated silicon 15,16 and carbon 18 vacancies has been verified theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…The annealing of vacancy-related defects has been studied by positron annihilation spectroscopy (PAS) 11,12,13,14 and electron paramagnetic resonance techniques (EPR) 15,16,17,18 in irradiated material. The identification of the EPR-centers as isolated silicon 15,16 and carbon 18 vacancies has been verified theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…17 The most common polytype encountered in recent positron studies for SiC is 6H, for which several values for bulk lifetime have been proposed, in the range of 136-150 ps. 8,[14][15][16]18,[20][21][22] The theoretical calculations give lifetimes of 134 ps for 4H-SiC, 23 141 ps for 6H-SiC, and 138 ps for 3C-SiC. 11 It should be noted that different calculation schemes ͑especially different enhancement factors͒ cause differences in the resulting absolute lifetimes, which become evident when comparing results from different studies.…”
Section: Vacancy Clustersmentioning
confidence: 96%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] ͒. These studies often involve irradiated materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, many works reported change of PAL in SiC irradiated by electron or ion beam [27][28][29][30][31][32][33]. Kawasuso et al reported that electron irradiated n-type (nitrogen-doped) 6H-SiC showed obvious change in τ ( 143 ps to 178 ps ), while p-type (aluminum-doped) 6H-SiC showed almost no change ( 136 ps to 138 ps ) [33]. The specimen was irradiated with 3 MeV electron to a fluence of 1×10 17 e − /cm 2 , that correspond to about 4×10 −6 dpa.…”
Section: Fig 4 Conventional γ-γ Coincidence Circuit-diagram To Measmentioning
confidence: 99%